Strengthening Early Childhood Literacy and Numeracy Through the GeLiNuBiLing Program (Environment-Based Numeracy Literacy Movement) at TK Garuda Surabaya - Innayatus Salisiy Salisiya; Tiara Nafa Dela Puspita; Ananda Aisyah Rahmawati; Rabiyya Museyibzada (Sustainable Human Capital Development Journal, 2025)
This study investigates the GeLiNuBiLing program, an environment-based literacy and numeracy initiative implemented at TK Garuda Surabaya. The primary objective is to understand its effectiveness in addressing the challenges faced by early childhood institutions in developing structured literacy-numeracy programs. Early childhood institutions often encounter obstacles in creating comprehensive literacy-numeracy programs due to limited infrastructure, teacher capacity, and access to appropriate learning materials. Additionally, these institutions must navigate the complexities of regulations that prohibit formal academic instruction while simultaneously meeting the needs of school readiness.To gain insights into the program’s impact, a qualitative case study was conducted. This study employed observation, interviews, and documentation as research methods. The data was analyzed using Miles and Huberman’s thematic analysis approach, supplemented by triangulation to enhance the validity of the findings. The GeLiNuBiLing program demonstrated its effectiveness in fostering children’s engagement, enhancing their number-letter recognition skills, and improving their observation writing abilities. Furthermore, the program successfully encouraged parental participation through the implementation of Home Story Corner activities. This study makes a unique contribution to the field by integrating learning management, teacher adaptability, and family engagement dimensions, which are often overlooked in previous research. The study’s findings are limited to a single institution and rely solely on qualitative data. The research provides valuable insights into sustainable human capital development and offers a practical model for resource-constrained PAUD institutions. By adopting contextual learning approaches, these institutions can effectively address the challenges they face in developing structured literacy-numeracy programs.